2014
DOI: 10.1016/j.imlet.2014.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics of bronchial biopsies: Galectin-3 as a predictive biomarker of airway remodelling modulation in omalizumab-treated severe asthma patients

Abstract: Asthma is a chronic inflammatory disease. Reticular basement membrane (RBM) thickening is considered feature of airway remodelling (AR) particularly in severe asthma (SA). Omalizumab, mAb to IgE is effective in SA and can modulate AR. Herein we describe protein profiles of bronchial biopsies to detect biomarkers of anti-IgE effects on AR and to explain potential mechanisms/pathways. We defined the bronchial biopsy protein profiles, before and after treatment. Unsupervised clustering of baseline proteomes resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(63 citation statements)
references
References 40 publications
3
60
0
Order By: Relevance
“…In a similar manner, proteomic profiling of endobronchial biopsies from asthmatics was used to determine predictors of response to anti-IgE antibody omalizumab. This revealed galectin-3, which is also an extracellular matrix protein involved in remodelling, as a biomarker of response [82]. This protein can be measured in urine and serum, and could be tested in future studies as a marker of response to therapy [83].…”
Section: Application Of Unbiased Techniques To Uncover Mechanisms Of mentioning
confidence: 95%
“…In a similar manner, proteomic profiling of endobronchial biopsies from asthmatics was used to determine predictors of response to anti-IgE antibody omalizumab. This revealed galectin-3, which is also an extracellular matrix protein involved in remodelling, as a biomarker of response [82]. This protein can be measured in urine and serum, and could be tested in future studies as a marker of response to therapy [83].…”
Section: Application Of Unbiased Techniques To Uncover Mechanisms Of mentioning
confidence: 95%
“…The authors divided the patients in the basis of whether they responded to treatment and performed a cluster analysis of baseline proteomes to pinpoint differences between groups on the protein level. It was demonstrated that administration of omalizumab downregulated bronchial smooth muscle proteins [72]. Moreover, among all ECM proteins, galectin-3 was the most reliable and predictive biomarker of airway remodelling modulation by omalizumab.…”
Section: Omalizumab and Airway Inflammationmentioning
confidence: 97%
“…No correlation was found between reduction in thickness of RBM and reduction in eosinophilic infiltration, possibly attributed to the limited number of patients. Interestingly, a proteomic analysis of bronchial biopsies was also performed by the same group on eight severe asthmatics before and after treatment with omalizumab for 1 year [72]. The authors divided the patients in the basis of whether they responded to treatment and performed a cluster analysis of baseline proteomes to pinpoint differences between groups on the protein level.…”
Section: Omalizumab and Airway Inflammationmentioning
confidence: 99%
“…In fact, galectin-3 was shown to be a reliable, stable and predictable biomarker of airway remodeling in omalizumab-responsive asthma patients. These patients had a more predominant extracellular matrix with contractile and structure proteins [39] . Galectins have been shown to be present in the lumen of intracellular vesicles containing glycoproteins destined to the apical site of epithelial cells and in thymic epithelial cells [40,41] ; so the regulatory role may include modulation of epithelial function in the development of the EMT.…”
Section: Discussionmentioning
confidence: 97%